2010
DOI: 10.1108/02610151011042402
|View full text |Cite
|
Sign up to set email alerts
|

Exploring ethnicity in organizations

Abstract: PurposeThe purpose of this paper is to explore how ethnicity remains relevant to the workplace experience of minority ethnic graduate employees in contemporary British organizations.Design/methodology/approachQualitative interviews were conducted with 30 British Black Caribbean graduate employees drawn from a range of public and private‐sector organizations to examine the ways in which they felt their ethnicity impacted on how they experienced their places of work. Template analysis was used to analyse the dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 39 publications
0
10
0
1
Order By: Relevance
“…British scholars have demonstrated how social class often closely intertwines with minority ethnicity. In one study, ‘black professional’ identities were as much about changing class status as ethnicity for early career graduates (Kenny and Briner, 2010). Another study indicated that early formative experiences of racism combined with social class transition enabled middle class blacks to signal class membership, minimising the probability of racial discrimination (Rollock et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…British scholars have demonstrated how social class often closely intertwines with minority ethnicity. In one study, ‘black professional’ identities were as much about changing class status as ethnicity for early career graduates (Kenny and Briner, 2010). Another study indicated that early formative experiences of racism combined with social class transition enabled middle class blacks to signal class membership, minimising the probability of racial discrimination (Rollock et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the black British Caribbean graduate in Kenny and Briner's (2010) study, the chief medical doctors in the present study all felt that they had to work harder to gain acceptance, which they may never gain in the end, as one of my interviewees put it. However, there is another strategy that is quite the opposite of working more, involving detaching oneself from the profession's career paths.…”
mentioning
confidence: 67%
“…Further areas of research that use TA include organisational research such as management and business (Kenny and Briner, 2010;McDowall and Saunders, 2010;Altinay et al, 2014), health (Howard et al, 2008), education (Au, 2007), sports science (Nash and Sproule, 2009) and tourism (Andriotis, 2010 cited in King, 2012, p. 427). TA studies vary in terms of size, from a single autobiographical case (King, 2008) to very large studies that may be considered large in qualitative terms, like 81 interviews by Donnelly (2008 cited in King, 2012, p. 427).…”
Section: Exploratory Study Methodsmentioning
confidence: 99%